2016
DOI: 10.1111/ijfs.13231
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect between Helichrysum italicum essential oil and cold nitrogen plasma against Staphylococcus aureus biofilms on different food‐contact surfaces

Abstract: Summary Staphylococcus aureus is the most common pathogen in human, and the most diseases produced by S. aureus are associated with biofilms. Helichrysum italicum essential oil (EO), as a natural and safe spice, was employed to disperse S. aureus biofilm by cold nitrogen plasma (CNP) assist. After S. aureus biofilm formation on food container surfaces, they were exposed to CNP and then treated with Helichrysum italicumEO for biofilm dispersion. The population of S. aureus biofilm was approximately reduced by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The majority of compounds possessing anti-biofilm activity are isolated from natural sources (Roy et al, 2018). A study by Cui et al (2016) observed not only the inhibitory effect of the essential oil of H. italicum against biofilm formation but also its ability to eradicate biofilm structure of S. aureus. The essential oil showed better activity in both aspects when compared with the effect of major essential oil component, neryl acetate, alone.…”
Section: Biofilm Prevention and Disruptionmentioning
confidence: 99%
“…The majority of compounds possessing anti-biofilm activity are isolated from natural sources (Roy et al, 2018). A study by Cui et al (2016) observed not only the inhibitory effect of the essential oil of H. italicum against biofilm formation but also its ability to eradicate biofilm structure of S. aureus. The essential oil showed better activity in both aspects when compared with the effect of major essential oil component, neryl acetate, alone.…”
Section: Biofilm Prevention and Disruptionmentioning
confidence: 99%
“…The antibacterial activity was evaluated in vitro and on fresh raw vegetables: water spinach, greens and lettuce to determine whether it has the potential to be used for vegetable preservation. Both sets of experiments showed that H. italicum inhibits the growth of E. coli and S. aureus [ 59 , 60 ]. Djihane et al (2017) proved the antibacterial and antifungal effects of immortelle EO as well.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of low-temperature plasma, the electric field acts as a catalyst for the formation of various reactive species such as oxygen free radicals (•O), hydroxyl free radicals (•OH), ozone (O 3 ), and nitrogen dioxide (NO 2 ) [70]. These reactive species primarily target amino acid residues on protein molecules, inducing structural and functional modifications [71]. One study demonstrated that the reduced IgG/IgE binding capacity of glycine, following medium barrier discharge plasma treatment, was associated with the oxidation of peptide bonds and sensitive amino acids like Trp, Tyr, and Phe [72].…”
Section: Oxidation Effect Of Active Particlesmentioning
confidence: 99%